A combination of LightOn gene expression system and tumor microenvironment-responsive nanoparticle delivery system for targeted breast cancer therapy - Xinyu Hou; Chenting Shou; Muye He; Jiajun Xu; Yi Cheng; Zeting Yuan; Minbo Lan; Yuzheng Zhao; Yi Yang; Xianjun Chen; Feng Gao (Elsevier, 2020)
A light-switchable transgene system called LightOn gene expression system could regulate gene expression with a high on/off ratio under blue light, and have great potential for spatiotemporally controllable gene expression. We developed a nanoparticle drug delivery system (NDDS) to achieve tumor microenvironment-responsive and targeted delivery of diphtheria toxin A (DTA) fragment-encoded plasmids to tumor sites. The expression of DTA was induced by exposure to blue light. Nanoparticles composed of polyethylenimine and vitamin E succinate linked by a disulfide bond, and PEGylated hyaluronic acid modified with RGD peptide, accumulated in tumor tissues and were actively internalized into 4T1 cells via dual targeting to CD44 and αvβ3 receptors. The LightOn gene expression system was able to control target protein expression through regulation of the intensity or duration of blue light exposure. In vitro studies showed that light-induced DTA expression reduced 4T1 cell viability and induced apoptosis. Furthermore, the LightOn gene expression system enabled spatiotemporal control of the expression of DTA in a mouse 4T1 tumor xenograft model, which resulted in excellent antitumor effects, reduced tumor angiogenesis, and no systemic toxicity. The combination of the LightOn gene expression system and NDDS may be an effective strategy for treatment of breast cancer.